USING THE THEORY OF PLANNED BEHAVIOR IN ACCOUNTING RESEARCH: A BIBLIOMETRIC REVIEW - Azmi, Zul; Puspita, Saftiara (Economic and Science Faculty of Islamic State University, 2024)
This research aims to map the use of the theory of planned behavior in accounting research which is written explicitly in articles in 2011-2023. This research explores the theory of planned behavior which is used as a theoretical basis for explaining phenomena within the scope of accounting. The method in this research uses a qualitative descriptive approach where data collection uses bibliometric review as a basis for analyzing research. The articles reviewed include Scopus indexed journal sources and Sinta 2 indexed journal sources. The research results show that based on the highest number of citations there are 3 Scopus articles in the field of financial and management accounting, 1 article in the field of environmental management, and 1 article in the field of psychology. As a comparison, the articles accredited by Sinta2 found 10 articles in the field of accounting. There is still more explicit use of the Theory of planned behavior in the Sinta 2 article. An interesting focus on the TPB, especially in light of the finding that there is not always a relationship between intentions and actual behavior. Several researchers highlight the need to strengthen intentions so that they can be translated into actual behavior, and the important role played perceived behavioral control in this process